Pengaruh Metode Pembelajaran Praktikum Perubahan Fisika dan Kimia Terhadap Hasil Belajar IPA Siswa - Melvin Aldila (Alpatih Harapan Semesta, 2026)
This research aims to evaluate the effectiveness of practical learning methods in improving student learning outcomes on the topic of physical and chemical changes at SMP Negeri 3 Cikancung. The method used is quantitative research with non-parametric statistical analysis. The normality test of the data shows that the data is not normally distributed with a p-value of 0.000, so the analysis continues with the Wilcoxon test. The Wilcoxon test results in a p-value of 0.000, indicating a significant difference between the initial and final scores of the students. The NGain percentage result is 78.11%, which is categorised as high. These findings indicate that the application of practical methods is effective in improving student learning outcomes. This research makes an important contribution to the development of more innovative and effective teaching methods in science education and highlights the need for the implementation of practical work in the education curriculum.